Anomalous Ambipolar Phototransistors Based on All‐Inorganic CsPbBr3 Perovskite at Room Temperature. Issue 21 (13th August 2019) - Zou, Yuting; Li, Feng; Zhao, Chen; Xing, Jun; Yu, Zhi; Yu, Weili; Guo, Chunlei
Abstract: Despite its extensive research in photovoltaics and light emitting diodes, the charge transport properties of all‐inorganic perovskite cesium lead bromide (CsPbBr3 ) remain elusive. Clarification of the intrinsic charge transport of this perovskite material is highly desirable, which will help to understand its working mechanism and fabricate high performance electronic devices. Here, it is demonstrated that the phototransistors based on CsPbBr3 microplates show anomalous ambipolar transport characteristics at room temperature. The hole mobility shows light dependence, while the electron mobility is identical under various light incidence. The hole mobility increases from 0.02 cm 2 V −1 s −1 (in dark conditions) to 0.34 cm 2 V −1 s −1 (50 mW cm −2 ); while the threshold voltage is shifted by 14 V when electron is the majority charge carrier. The anomalous transport behavior can be attributed to the photovoltaic and photoconductive effects. Moreover, the device shows photoresponsivity and detectivity up to 110 mA W −1 and 4.5 × 10 13 Jones, respectively, under 532 nm laser illumination. This research unveils the charge transport mechanism of CsPbBr3 perovskite, provides more evidence and will thus contribute to the perovskite electronic and optoelectronic researches. Abstract : Unveiling the intrinsic charge transport property is key to the fundamental research and potential applications of perovskite. Here it is demonstrated that CsPbBr3 shows anomalous ambipolar transport under light illumination at room temperature. The phenomenon is proved to be due to the photoconductive and photovoltaic effects.